The effect of abo and rh blood group antigens on admission to intensive care unit and mortality in patients with COVID-19 infection - Yaylacı,Selçuk (2020)
SUMMARY AIM The aim of this study is to analyze the prognostic significance of ABO and Rh blood group antigens along with various parameters in patients followed-up with the diagnosis of COVID-19. METHODS We evaluated 397 patients who were follow-up and treated due to COVID-19 infections. The ages, genders, chronic diseases, ABO and Rh blood group antigens, admission rates to Intensive Care Units (ICU), and mortality rates of the patients were analyzed. FINDINGS The mean age of the 397 patients with COVID-19 was 47±17 years. In the blood group analysis of the patients, A Rh-positive (A +) was the most frequently seen blood type (176 patients, 44.3%) followed by O Rh-positive (0 +) (109 patients, 27,5%); 38 patients were Rh negative (Rh -) (9,6%). 53 of the patients (13,4%) were followed in ICU and 29 patients died (7,3%). Neither mortality nor admission to ICU was seen for Rh – group. The comparison of Rh groups concerning the need for ICU admission revealed a significantly high rate of ICU admission in the Rh + group (p=0,011), while no significant relationship was found between mortality and Rh antigen (p=0,069). CONCLUSION The most frequently seen blood type among COVID-19 patients was A +. The Rh + blood group was found in all cases who were admitted to ICU and had a death outcome. The Rh + blood group was found in a significantly high number of patients who were admitted to ICU, while no significant relationship was found between mortality and Rh blood group.